A mirror based scheme of a laser projection microscope; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Gubarev F. A. Fedor Aleksandrovich (Integrated Computer Control Systems in Mechanical Engineering, 2016)
Title screen